Nouveaux modèles économiques et renouvellement productif à Romans-sur-Isère : à la recherche de la durabilité territoriale - Florian Fompérie; Muriel Maillefert (EchoGéo)
Faced with deindustrialization, the city of Romans-sur-Isère has recently adopted a strategy of redeployment of its activities based on an heritage model. This work focuses on the transformative dimension of the economic model adopted by crossing two paradigms: new economic models and the circular economy. It examines the degree of transformation of this industrial model through five emblematic experiments. These experiments serve as a basis for proposing and identifying the characteristics of an innovative model. The analysis thus allows us to show the stakes of a change of model towards a sober and servicial model.